Brain MRI Growth Patterns in Neurofibromatosis 1 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Brain growth patterns in 27 children with neurofibromatosis 1 (NF-1) (20 boys, aged 1.0-17.7 years; mean age, 8.8 years) were compared to 43 controls (22 boys, aged 0.1-17.7 years; mean age, 5.9 years) using magnetic resonance imaging (MRI) in a study at Children's Medical Center, Hartford, Connecticut.